Union formation, marriage and first birth: Convergence across cohorts in Austria, Hungary, Northern Italy and Slovenia? - Marija Mamolo (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
The interplay between changes of different demographic determinants may trigger or prevent convergence of various dimensions of demographic behaviour both within and between countries of western and Eastern Europe. We investigate whether convergence or divergence dynamics prevail across cohorts in Austria, Hungary, northern Italy and Slovenia with regard to union formation and transition to motherhood. Our findings suggest that convergence in patterns of union formation and first birth is far from being achieved across the countries considered. Postponement of family formation and motherhood has spread, but between-country differences persist and even suggest diverging cross-country patterns.
Keywords: 300; Union formation; marriage; first birth; childbearing; convergence; Ehe; Fertilität; Schätzung; Vergleich; Österreich; Ungarn; Italien; Slowenien